Fabrication of Nd:YAG transparent ceramics by non-aqueous gelcasting and vacuum sintering. Issue 10 (August 2016) - Yin, Rui; Li, Jiang; Dong, Manjiang; Xie, Tengfei; Fu, Yuelong; Luo, Wei; Ge, Lin; Kou, Huamin; Pan, Yubai; Guo, Jingkun
Abstract: Highly transparent Nd:YAG ceramics were fabricated by non-aqueous gelcasting and vacuum sintering for the first time, using epoxy resin and polyamine curing agent as gelling system. The influences of dispersant, solid loading and the organics of gelling system on the viscosity of suspensions and the stability of suspensions were discussed. The optimized nonaqueous slurry was of 54 vol% solid loading, comprising the commercial α-Al2 O3, Nd2 O3 and Y2 O3 powders. The slurry with low viscosity and good fluidity was obtained by using 0.45 wt% PEI as dispersant. The homogenous and dense green body was obtained through solidificating the slurry in-situ. The green body after burnout had a relative density of 55.0% with a narrow pore size distribution. The transmittance of the Nd:YAG ceramics sintered at 1775 °C for 30 h with the thickness of 1.5 mm reached 83% at 1064 nm. The average grain size of the sample was about 71 μm.